Development of a Portable Gait Rehabilitation System for Home-Visit Rehabilitation - Hiroaki Yano; Naoki Tanaka; Kiyotaka Kamibayashi; Hideyuki Saitou; Hiroo Iwata (The Scientific World Journal)
This paper describes the development of a gait rehabilitation system with a locomotion interface (LI) for home-visit rehabilitation. For this purpose, the LI should be compact, small, and easy to move. The LI has two 2 degree-of-freedom (DOF) manipulators with footpads to move each foot along a trajectory. When the user stands on the footpads, the system can move his or her feet while the body remains stationary. The footpads can have various trajectories, which are prerecordings of the movements of healthy individuals walking on plane surfaces or slopes. The homes of stroke patients may have not only flat surfaces but also some slopes and staircases. The quadriceps femoris muscle is important for walking up and down slopes and staircases, and the eccentric and concentric contractions of this muscle are, in particular, difficult to train under normal circumstances. Therefore, we developed a graded-walking program for the system used in this study. Using this system, the user can undergo gait rehabilitation in their home, during visits by a physical therapist. An evaluation of the results of tests showed that the vastus medialis muscles of all the subjects were stimulated more than by walking on real slopes.